Enhancement of SME feasibility through the integration of BMC, functional organization, and SCM - Endang Chumaidiyah; Putri Maulani Fauzi; Anton Abdulbasah Kamil (Cogent Business & Management, 2024)
Various studies indicate that resources pose one of the primary challenges for SMEs in enhancing their performance. Existing theories and concepts are often impractical and too complex to be applied effectively in improving SME performance and feasibility due to resource limitations. This paper aims to design a model for strengthening the performance and feasibility of SMEs, particularly micro-industries, by integrating three crucial approaches: business model canvas, functional organization, and supply chain management. The resulting model, named `Feasibility Model for SMEs,' can serve as a simple and practical solution by focusing on key variables resulting from the integration of these three approaches. The research methodology involves a literature review and conceptual research to design the SME performance enhancement model. Subsequently, the model is applied to SME cluster X. Quantitative research is conducted using smart PLS tools to confirm the theory and test hypotheses regarding the design model for 50 SMEs. The model testing results indicate that supply chain, production, value proposition, and marketing are significant variables for enhancing SME performance. The model designed in this study is novel and highly practical for enhancing SME feasibility focusing on five variables, namely supply chain, production, value proposition, marketing, and performance.
Keywords: 650; BMC; SCM; Integration; Performance; Feasibility; SMEs